2019
DOI: 10.1177/0144598719872802
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the mud shale reservoirs in coal-bearing strata and resources evaluation in the eastern margin of the Ordos Basin, China

Abstract: As the co-exploration and co-production of unconventional gas have become a new trend of the unconventional gas exploration and development in the eastern margin of the Ordos Basin, this study focuses on the distribution, pore characteristics, geochemical properties, and mineral composition of the mud shale in the coal-bearing strata. The results show that the mud shale in the coal-bearing strata is distributed relatively stably with an average cumulative thickness of 77.60 m and a buried depth of 200–2400 m, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 75 publications
1
5
0
Order By: Relevance
“…Generally, the higher smooth granules (clay), the higher Corganic content will be found in the mangroves area. This is consistent with study conducted by Serrano et al (2016) and Chen et al (2020) that clay has a good ability to storage C-organic because it has dense pores while sand has large pores so that organic matter is easily carried by currents. The C-organic content in the substrate is very important as a source of nutrients for gastropods in the mangrove ecosystems.…”
Section: Association Of Gastropods and Environmental Characteristicssupporting
confidence: 92%
“…Generally, the higher smooth granules (clay), the higher Corganic content will be found in the mangroves area. This is consistent with study conducted by Serrano et al (2016) and Chen et al (2020) that clay has a good ability to storage C-organic because it has dense pores while sand has large pores so that organic matter is easily carried by currents. The C-organic content in the substrate is very important as a source of nutrients for gastropods in the mangrove ecosystems.…”
Section: Association Of Gastropods and Environmental Characteristicssupporting
confidence: 92%
“…The coal measure strata in the study area are the Benxi Formation, Taiyuan Formation, and Shanxi Formation from bottom to top. The sedimentary system dominated by barrier coast lagoon system is developed in the Benxi Formation and Taiyuan Formation, while the coastal shallow sea lagoon tidal delta sedimentary system is developed in Shanxi Formation, which is a typical marine land transitional facies sedimentary environment [25][26][27][28]. The coal measure strata of these different sedimentary systems have different reservoir combinations of "coalbed methane-tight sandstone gas-shale gas."…”
Section: Samples and Methodsmentioning
confidence: 99%
“…Previous studies have shown that the pore structure of coal measure shale is affected by many factors. In China, studies on coal measure shales of Taiyuan Formation in Huainan coalfield, Shanxi Formation, and Taiyuan Formation in Qinshui Basin have found that organic matter can promote the development of nanoscale pores (Chen et al, 2020; Ge et al, 2020; Pan et al, 2017), significantly promoted the pore development of <50 nm, followed by the content of clay minerals, while quartz inhibited the pore development (Yan et al, 2017; Yuan et al, 2021). However, Zhang et al (2017) studied the pore structure of coal measure shales of Yan’an Formation and Taiyuan Formation in the northeastern margin of the Ordos Basin and found that organic matter and clay content had a poor correlation with total surface area and porosity, and believed that single factor had no significant influence on pore structure (Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%